Extending Telecommunications Service to Rural Areas-The Chilean Experience : Awarding Subsidies Through Competitive Bidding - Wellenius, Björn (World Bank, Washington, DC, 2012)
Chile's telecommunications market is one of the most open and competitive in the world. Nevertheless, about 10 percent of all Chileans that live in localities do not even have a public telephone. To increase access to public telephones in rural and low-income urban areas, the Chilean government set up a special fund in 1994. The fund, due to expire in 1998, is financed by the national budget and administered by a council chaired by the telecommunications minister. The council decides on the annual program of projects eligible for subsidy and awards the projects and subsidies through competitive bidding. The fund's second round began in August 1996. With successful completion of the 1996 round, more than 97 percent of Chileans will likely have access to basic telecommunications by 1998, and the fund may well have a surplus. This Note describes the Chilean experience and the lessons that may be broadly applicable in other emerging economies.